Estilos de personalidad y estrategias de afrontamiento al estrés en soldados : un estudio correlacional (2015)
ABSTRACT: This study looked into the relationship between personality styles and coping strategies in soldiers who are in initial training in one rural region of Antioquia. The sample consisted of 68 male participants between the ages of 18 and 24. Participants were assessed with the Millon Inventory of Personality-MIPS and the Escala de Estrategias de Coping-EEC-M. Results show correlations between Social support and personality styles such as Nurturing, Externally Focused, Outgoing and Agreeing. Cognitive avoidance correlated negatively with Thought. The latter reached the highest percentile and is considered a useful cognitive style for soldiers in their service due to the fact that, under pressure and risky circumstances, the analysis of the situations must be cautious and methodical.